The effects of Nordic and general walking on depression disorder patients’ depression, sleep, and body composition - Yu, Seong Hun; Park, Seong Doo (Journal of Physical Therapy Science, 2015)
[Purpose] This study examined Nordic walking as an exercise intervention for the elderly with depression. [Subjects] Twenty-four patients who were diagnosed with depression were randomly selected and divided into two groups, an experimental group which performed Nordic walking, and a control group, which performed normal walking. [Methods] Both groups practiced their respective walking exercise for 50 minutes per day, three times a week for eight weeks. To compare the effects of the intervention, psychological factors using the Beck depression inventory and sleep quality was assessed using the Korean version Pittsburgh sleep quality index. Skeletal muscle mass, fat free mass, body mass index, body fat percentage, and basal metabolism were estimated three times by a body composition analyzer, before the intervention, four weeks after the intervention, and eight weeks after the intervention. [Results] There was a significant difference in depression with a main effect of time in both groups. There was also a significant difference in sleep in over time and interaction. The differences over time between the two groups were significant for depression, sleep, and skeletal muscle mass. [Conclusion] The results suggests that Nordic walking has a positive effect on depression and sleeping disorders of the elderly, suggesting that Nordic walking based exercise programs should be developed for the elderly who suffer from depression or a sleeping disorder.